(untitled) - Kohls, Richard L. (Upper Saddle River, NJ, 2002)
The ninth edition of Marketing of Agricultural Products contains completely updated content, tables, figures, and references including the 1997 Census of Agriculture and Business, as well as Trade data, and U.S. Department of Agriculture studies. It blends marketing and economic theory with real world analytical tools to assist readers in better understanding the food system and making profitable marketing decisions. This edition includes increased treatment of food value-adding and marketing management, including advertising, new product development, sales promotion, pricing, and logistics. For farmers, consumers, or those in food marketing.
Phân tích giá trong thị trường nông nghiệp,Tổ chức vận hành thị trường
Keywords: Farm produce,Sản phẩm nông nghiệp; Marketing,Tiếp thị